An aircraft boarding model accounting for group behavior. (June 2018) - Tang, Tie-Qiao; Yang, Shao-Peng; Ou, Hui; Chen, Liang; Huang, Hai-Jun
Abstract: The rapid increase of civil aviation has posed a great challenge to air traffic (especially aircraft boarding). In this study, we propose a new aircraft boarding model to explore the impacts of group behavior on each passenger's motion, seat conflict, check-in time, time of handling luggage as well as boarding time during the boarding process. The numerical results show that the group behavior has some positive impacts on the boarding efficiency, and that the impacts become more prominent with an increasing number of groups. Hence, the group behavior should be encouraged to enhance the efficiency during the boarding process. Highlights: Propose an aircraft boarding model accounting for group behavior. Simulate the impacts of group behavior on each passenger's boarding behavior. Evaluate the boarding efficiency.